2016
DOI: 10.1177/016146811611801206
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Adolescents Attending Progressive and No-Excuses Urban Charter Schools to Analyze, Navigate, and Challenge Race and Class Inequality

Abstract: Background/Context Sociopolitical development (SPD) refers to the processes by which an individual acquires the knowledge, skills, emotional faculties, and commitment to recognize and resist oppressive social forces. A growing body of scholarship has found that such sociopolitical capabilities are predictive in marginalized adolescents of a number of key outcomes, including resilience, academic achievement, and civic engagement. Many scholars have long argued that schools and educators have a central role to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 69 publications
3
18
1
Order By: Relevance
“…In addition, school engagement was higher in the high critical consciousness group than in the low critical consciousness group. In contrast to others, Seider et al (2016) found no relation between grade point average (measured at the beginning of 9th grade) and critical reflection skills (measured at the end of 9th grade).…”
Section: Systematic Review Of the Critical Consciousness Literature I...contrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, school engagement was higher in the high critical consciousness group than in the low critical consciousness group. In contrast to others, Seider et al (2016) found no relation between grade point average (measured at the beginning of 9th grade) and critical reflection skills (measured at the end of 9th grade).…”
Section: Systematic Review Of the Critical Consciousness Literature I...contrasting
confidence: 99%
“…Research on these curricula—including, for example, case–control studies comparing schools implementing a particular curriculum to matched schools that have not implemented the curriculum—could shed light on how content and pedagogy contribute to the development of critical consciousness and would be policy-relevant, given that several states now mandate the inclusion of ethnic studies in K–12 settings (see Dee & Penner, 2017). The work of Seider and colleagues (Seider et al, 2016) provides foundational knowledge on how different schooling models (progressive vs. no excuses) promote growth in distinct dimensions of critical consciousness (critical reflection and critical motivation, respectively), raising exciting prospects for work that examines how practices from each model might be integrated into the other to promote broader growth in critical consciousness. In addition, work examining alternative pedagogical models and work examining traditional public and private schools (in contrast to the charters that were the focus of Seider et al’s study) will extend this critical area of research.…”
Section: Bringing It Together and Setting A Research Agenda: Perspect...mentioning
confidence: 99%
See 1 more Smart Citation
“…This study provides rigorous longitudinal evidence suggesting that experiences that engage youth in challenging rather than avoiding societal inequalities may foster career development and occupational attainment among marginalized youth. This evidence supports conceptual (e.g., Ladson-Billings, 2009) and empirical arguments (e.g., O’Connor, 1997; Ramos-Zayas, 2003; Cabrera et al, 2014; Dee & Penner, 2016; Seider et al, in press) for directly addressing the inequalities constraining marginalized youth—for example, via engagement in critical action. There are various avenues that may engender this engagement, such as ethnic studies curricula, participatory action research, and other critically informed practices that focus on social action and inequality, both inside and outside of schools.…”
Section: Discussionsupporting
confidence: 67%
“…Collectively, these findings suggest that policies and practices, including interventions, that target the social identity threats and sociopolitical constraints that marginalized youth face may, somewhat paradoxically, foster educational and occupational success. CC-informed interventions such as Tucson’s Mexican American studies (MAS) program (e.g., Cabrera et al, 2014; Cammarota & Romero, 2009), San Francisco’s ethnic studies curricula (Dee & Penner, 2016), social psychological interventions (Rapa, 2016), and schooling approaches (Ramos-Zayas, 2003; Seider et al, in press), as well as reviews of these approaches (Watts & Hipolito-Delgado, 2015), suggest specific program elements and strategies to target the development or enactment of critical action.…”
Section: Discussionmentioning
confidence: 99%